Ekonometryczne modelowanie cykliczności w procesach sprzedaży na podstawie danych dziennych - Kufel, Tadeusz (Econometric Modelling of Periodicity in Sale Processes for Daily Data, 2006)
The purpose of the paper is to present the problem of sale modelling for daily data with regard to the issue of modelling the complex periodicity, i.e. annual, monthly, weekly cycle. In the paper it has been indicated that the model with periodic dummies outperforms the trigonometric polynomial in describing the complex periodicity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 236-247